Pendampingan Karang Taruna dalam Proses Konservasi Lingkungan Pesisir Teluk Tomini di Desa Payunga Kecamatan Batudaa - Sri Rumiyatiningsih Luwiti; Indri Wirahmi Bay (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
Real Work Lecture (KKN) is a community service activity in a particular area as an implementation of Tri Dharma College. KKN activities aim to provide field experience to students about the condition of society directly and also to form an independent attitude and responsibility in carrying out KKN activities. The implementation of KKN began from September 15 to November 3, 2021 in Payunga Village, Batudaa District, Gorontalo Regency. The program conducted in Payunga Village includes socializing the core program, namely the utilization of hyacinths in limboto lake, devotional work every Saturday, badminton sports activities, studies every Saturday night, and planting tongue-in-law flowers next to the batudaa highway of payunga village. In general, thematic KKN activities carried out in Payunga Village of Batudaa Subdistrict, Gorontalo Regency went well because the community response was also good. The implementation of the Thematic KKN programs is expected to benefit the community.